The immunostimulant effect of jamblang stem bark (Syzygium cumini L.) ethanol extract against mice macrophages phagocytosis activity and capacity - sari, widya; safitri, novi; izzazaya, annisa; Kusuma, Hendrix Indra; Syahfitri, Widya; Rosnizar, Rosnizar (Jurnal Natural, 2025)
This study aims to determine the effect of administering Jamblang Stem Bark Ethanol Extract (Syzygium cumini L.) (JSBEE) on the activity and phagocytosis capacity of macrophages in mice (Mus musculus) infected with Staphylococcus aureus bacteria. The research method used a completely randomized design (CRD) with five treatments and five repetitions, conducted in-vitro and in vivo test. The treatments for in vitro involved administering distilled water (T0), Stimuno (T1), and JSBEE at concentrations of 10 ppm (T2), 100 ppm (T3), and 1000 ppm (T4). Subsequently, in vivo treatment was conducted using distilled water (T0), stimuno (T1), JSBEE at 10 mg/kg (T2), 100 mg/kg (T3), and 1000 mg/kg (T4). Initially, mice underwent in vivo administration of JSBEE, administered orally via catheter tip, with a dosage of 1 mL per 10 g of body weight. JSBEE was administered orally for 10 days, followed by infection with S. aureus on the 11th day. The in vitro tests were conducted by isolating macrophage cells from the intraperitoneal fluid, to which S. aureus and JSBEE were added. Intraperitoneal fluid collected from the mice was used to prepare smears using the thin blood smear method and Giemsa staining. Macrophage phagocytosis activity was observed and assessed based on the percentage activity formula, and the phagocytic capacity of macrophages was measured by the number of S. aureus cells phagocytosed. The results indicated that JSBEE significantly affected (P0.05) both the activity and phagocytic capacity of macrophages in vivo and in-vitro. The best concentration of JSBEE for increasing both the activity value and phagocytic capacity of macrophages was 100 ppm (T3).